Urban cracks: the agency of the headquarters Luz do Faroeste and Teatro de Contêiner in the territory of Luz (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This paper discussed the creation of space-time cracks in the hegemonic capitalist/colonial system, and consequently, in the territory through which it (re)configures itself - the city -, through the headquarters of theater groups. From this perspective, this text investigated the creation and performance of Luz do Faroeste and Teatro de Contêiner - respectively the headquarters of the theater groups Pessoal do Faroeste and Cia. Mungunzá - in the territory of Luz, located in the central region of the city of São Paulo.
Keywords: Headquarters of theater groups; City; Space-time cracks